A modification of Nissen fundoplication improves patients' outcome and may reduce procedure-related failure rate. (February 2017) - Bardini, Romeo; Rampado, Sabrina; Salvador, Renato; Zanatta, Lisa; Angriman, Imerio; Degasperi, Silvia; Ganss, Angelica; Savarino, Edoardo
Abstract: Background: Laparoscopic anti-reflux surgery has a failure rate of 10–20%. We aimed to investigate whether a modification of Nissen fundoplication (MNF) may improve patients' outcome and reduce failure rate. Materials & methods: We prospectively compared 40 consecutive patients with gastroesophageal reflux disease who underwent anti-reflux surgery: 20 Nissen fundoplication (NF) and 20 the MNF approach. Eight cases in the MNF group needed redo surgery. The MNF consisted in suturing the esophagus to the diaphragmatic crura on each side by means of 4 non-absorbable stitches and in fixing the upper stitch of the valve to diaphragm. In case of clearly weak crura, a reinforcement with Ultrapro mesh was used. All patients were assessed before and after surgery using validated symptoms and quality of life (GERD-HRQL) questionnaires, manometry and 24-h impedance-pH monitoring, endoscopy and barium-swallow. Results: Mortality and postoperative complications were nil. At a median follow-up of 36 months, no significant differences emerged between the MNF and NF group in terms of symptoms, GERD-HRQL scores, manometric findings, and impedance-pH features. Dysphagia was not reported by the MNF group, while it was quite common (20% vs.0%, p = ns) in the NF group. Anti-reflux surgery was successful in all patients in the MNF group, whereas two patients in the NF group presented a slipped wrap and one recurrent reflux; two of these cases required redo-surgery (10% vs. 0%, p = ns). Conclusions: Our preliminary data demonstrated that the MNF is a safe and effective procedure. Further, it seems to reduce the failure rate associated to the surgical procedure. Highlights: Laparoscopic anti-reflux surgery has a failure rate of 10–20%. We aimed to investigate whether a modification of Nissen fundoplication (MNF) may reduce failure rate. The MNF consisted in suturing the esophagus to the diaphragmatic crura and the upper stitch of the valve to diaphragm. Our preliminary data demonstrated that MNF is a safe and effective procedure. MNF seems to reduce the failure rate associated to the surgical procedure.